The inestability as a rutine. Precarization of ordinary life and its impact in food consumption in Buenos Aires – Argentina - Aguirre, Patricia; Diaz Córdova, Diego (Revista de Antropología Social, 2021)
This article discussed some of the changes that suffered food consumption in Argentina in the last 30 years and its impact on food security´s components (availability, access, biological utilization and stability). All these changes led to precarization of consumption as a new normality. We described the contextual situation through National Expenditure Surveys and Nutrition and Health Surveys. We look for changes in food baskets with our own field work and through semi-structured interviews in different households income sectors. We want to understand the consumer practices in order to keep or increase and the reasons they made that. As the opposite of the routine (with its repeating charge and safety), precarization involves one permanent alert against an unsafe present and unpredictable future.